The Effect of Propolis Ethanolic Extract on the degree of lung damage of mice (Mus musculus) which induced by cigarette smoke - . ismael; Diding Hery Prasetyo; Riza Novierta Pesik (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2015)
Background: The Propolis ethanolic extract contains a variety of potent antioxidants, especially flavonoids and Caffeic Acid Phenylethyl Ester (CAPE). Flavonoids have a very strong antioxidant effect against free radicals capable of cigarettes. Meanwhile, CAPE is a potent inhibitor of Nuclear Factor kappa-light-chain-enhancer of activated B cell (NF-kB). Nuclear Factor kappa-light-chain-enhancer of activated B cell (NF-kB) is an essential mediator of inflammation. This study aims to demonstrate the effect of ethanolic extract of propolis can reduce the degree of lung damage of mice induced by cigarette smoke. Methods: This was a laboratory experimental research the posttest only control group design. Samples were twenty five mices Swiss Webster type (age 2-3 months; weight 20-30 gram) divided into 5 groups, each group has five mices. Mices for Control Group (KK) and Induction Group (KI) were administered by aquadest. While, the first Treatment Group (KP1), the second Treatment Group (KP2) and the third Treatment Group (KP3) were administered propolis ethanolic extract by dose 5.6 mg/20 g weight of mice, 11.2 mg/20 g weight of mice, and 16.8 mg/20 g weight of mice respectively. All groups except KK, were induced by smoke of one cigarette stick per day before extract administration. This research was done for 14 days. On day 15th, the mice were killed and lung organ was isolated and prepared histologically using paraffin method and then stained with haematoxylin and eosin (HE). The Data were analyzed by using Kruskall Wallis (? = 0.05) and continued by Mann Whitney (? = 0,05). Results: The results of Kruskall Wallis test showed that there was significant difference between five-groups. Mann Whitney test results showed there was significant difference between grups of KK-KI, KI-KP1, KI-KP2,KI-KP3, KP1-KP2,KP1-KP3 and KP2-KP3. Conclusion: Propolis ethanolic extract decreasethe degree of lung damage of mice (Mus musculus) which induced by cigarette smoke. Keywords: Propolis ,cigarette smoke, degree of lung damage, mice.